Demographic Change and Economic Well-Being : The Role of Fiscal Policy. (International Monetary Fund, 2016)
This paper discusses the role of fiscal policy and demographics. By the end of this century, about two-thirds of all countries are expected to have declining populations. This will have profound implications for economics, financial markets, social stability, and geopolitics. Fiscal policy responses and technological innovation are especially important parts of the solution. Without action, public pension and health systems will not be sustainable over the long term. The increase in life expectancy and economic welfare that came with the industrial revolution brought with it the seeds of demographic change. This is a demographic double whammy that will have major implications for economic growth, financial stability, and the public purse. With declining fertility rates, populations in some advanced economies did not just grow more slowly; they stagnated or began to shrink. IMF analysis suggests that, if everyone lived three years longer than expected, pension related costs could increase by 50 percent in both advanced and emerging economies. This would heavily affect private and public sector balance sheets and could also undermine financial stability.